“The Boundary of the World” – The Beginnings of Tourism in the Bieszczady Mountains in the 19th Century - Organ, Michał (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
The article fills the gap in the knowledge of the history of tourism in the Western Bieszczady, presenting its beginnings in the 19th century. This area was rarely visited, as it was not perceived as attractive; the beginnings of tourist “exploration” date back to the 19th century. The analysis is based on diary accounts, memoirs, press articles and the first travel guides. In the preserved reports, the Bieszczady Mountains appear as a wild, inaccessible area, devoid of the road infrastructure necessary for travelers. The wilderness of Bieszczady was traversed for sentimental, social, commercial, religious and health reasons, initially on foot or on horseback.

Artykuł uzupełnia lukę w stanie wiedzy o historii turystyki w Bieszczadach Zachodnich, prezentując jej początki w XIX w. Teren ten był rzadko odwiedzany i choć nie postrzegano go jako atrakcyjnego, początki turystycznej „eksploracji” sięgały XIX w. Analiza opiera się na relacjach pamiętnikarskich, wspomnieniach, artykułach prasowych oraz pierwszych przewodnikach turystycznych. W zachowanych relacjach Bieszczady jawią się jako dziki, nieprzystępny obszar, pozbawiony infrastruktury drogowej koniecznej dla podróżnych. Bieszczadzkie bezdroża pokonywano z pobudek sentymentalnych, towarzyskich, handlowych, religijnych i zdrowotnych, początkowo pieszo bądź konno.
Keywords: Bieszczady; tourism; history of tourism; memoirism; travels; turystyka; historia turystyki; pamiętnikarstwo; podróż